LEGAL RECONSTRUCTION FOR AUTONOMOUS VEHICLE USE IN INDONESIA: CHALLENGES AND SOLUTIONS IN THE AGE OF ARTIFICIAL INTELLIGENCE - Djohan, Naufal Hasanuddin; Indarti, Erlyn; Malik, Muhammad Fahad (Masalah-Masalah Hukum, 2025)
This research explores the urgent need for a legal framework governing the use of Autonomous Vehicles (AVs) in Indonesia, focusing on the integration of Artificial Intelligence (AI) technologies in transportation. With traffic accidents accounting for a significant portion of global fatalities, the adoption of AVs powered by AI is seen as a potential solution to reduce human errors and enhance road safety. However, Indonesia’s existing traffic laws, primarily focused on conventional vehicles, lack provisions for AVs, creating a legal vacuum. This study compares the legal structures of AVs in the United Kingdom and Indonesia, highlighting the differences in recognition, liability, and regulation. Drawing on the concept of "Law as Integrity" by Ronald Dworkin, this paper argues for the construction of a new legal framework that integrates the evolving needs of society, technology, and legal principles. By applying a multi-disciplinary approach, the research emphasizes the importance of collaborative legal construction, involving government, academia, civil society, and manufacturers, to ensure safe, just, and efficient integration of AVs in Indonesia’s road systems. The study concludes with recommendations for regulatory reforms, including the establishment of specialized supervisory agencies and the mapping of AV operational areas.